OPTIMIZATION OF THE NUMBER OF DUMP TRUCKS USING QUEUING THEORY TO MINIMIZE THE LOADING AND HAULING COST OF OVERBURDEN AT BATU HIJAU MINE PT AMMAN MINERAL NUSA TENGGARA - Widjaja, Michael
The main activity in the mining industry is the hauling of material from one place to another. One part of the operational costs directly related to this activity is the production unit costs of material hauling. By optimizing the amount of dump truck used, the production unit costs of material hauling can be reduced to a minimum. To be able to carry out material removal activities effectively and efficiently, a method of optimizing the number of dump trucks is needed. The method used in this study is queuing theory because it can simulate waiting times and the number of queues that occur from various variations of the number of dump trucks used in the material removal system. This research was conducted at the Batu Hijau Mine of PT Amman Mineral Nusa Tenggara which uses a conventional truck and shovel mining system to move overburden material from the mining front to waste dump. In this study, it is assumed that there are only four service nodes in the overburden material removal cycle queuing system, namely overburden material loading on the work front, transporting overburden material to the waste dump, overburden material disposal in the waste dump, and returning to the work front. The purpose of this study is to determine the cheapest loading and transportation costs based on the optimal number of dump trucks. By varying the number of dump trucks used in this queuing system, ten dump trucks resulted in the lowest production unit costs. It is $ 0.770/ton of overburden material.